Yield Components and Nutritional Analysis of Eggplant (Solanum melongena L.) Under Varying Rates of Vermicast Fertilizer - Mohammad Dollison; Merly O. Tapas (Universidade Estadual de Alagoas, 2024)
This study was conducted in a farmer's field at Balantay, Dimasalang, Masbate, Philippines, to evaluate the performance of different eggplant varieties with different levels of vermicast fertilizers. The different varieties were arranged in the plot while the levels of vermicast applied were set in the sub-plot using a two-factorial design in a Randomized Complete Block Design (RCBD). Growth parameters such as the number of days to flowering and plant height at maturity were evaluated. The fruit yield and other parameters like yield per treatment in kgs, number of marketable fruits, number of non-marketable fruits, yield per hectare basis, and the chemical analysis of the nutritional value of eggplant fruits were also gathered. Based on the result of the study, growth parameters, and yield performance, particularly on the number of days to flowering, plant height in cm at maturity period, yield per treatment in kilograms, number of marketable fruits, number of non-marketable fruits, and yield in tons were significantly affected by the varying levels of vermicast application. However, a non-significant result was observed between different varieties of eggplant. For nutritional analysis, it was found that the application of higher rates of vermicast (10 tons/ha) resulted in a higher calcium, magnesium, and sodium content. In light of these findings, applying vermicast at 10 tons/ha as a substitute for synthetic fertilizer in eggplant production is recommended for a higher fruit yield and better farm profit.